2017
DOI: 10.1126/science.aan2329
|View full text |Cite
|
Sign up to set email alerts
|

Egg accumulation with 3D embryos provides insight into the life history of a pterosaur

Abstract: Fossil eggs and embryos that provide unique information about the reproduction and early growth of vertebrates are exceedingly rare, particularly for pterosaurs. Here we report on hundreds of three-dimensional (3D) eggs of the species from a Lower Cretaceous site in China, 16 of which contain embryonic remains. Computed tomography scanning, osteohistology, and micropreparation reveal that some bones lack extensive ossification in potentially late-term embryos, suggesting that hatchlings might have been flightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 23 publications
(17 reference statements)
4
45
1
1
Order By: Relevance
“…Furthermore, the absence of the endosteal lamella suggests that this bone belongs to a juvenile. In Hamipterus and some anhanguerid pterosaurs the size variation is reflected in the osteohistological pattern of each bone (Sayão 2003, Wang et al 2014, which establishes a correlation between size difference and ontogenetic development (Wang et al 2014(Wang et al , 2017. the osteohistological features of this specimen are consistent with a juvenile but not e20190768 17 | 32 a neonate (see Wang et al 2017 for histological structures of neonates and embryos).…”
Section: Osteohistologymentioning
confidence: 71%
“…Furthermore, the absence of the endosteal lamella suggests that this bone belongs to a juvenile. In Hamipterus and some anhanguerid pterosaurs the size variation is reflected in the osteohistological pattern of each bone (Sayão 2003, Wang et al 2014, which establishes a correlation between size difference and ontogenetic development (Wang et al 2014(Wang et al , 2017. the osteohistological features of this specimen are consistent with a juvenile but not e20190768 17 | 32 a neonate (see Wang et al 2017 for histological structures of neonates and embryos).…”
Section: Osteohistologymentioning
confidence: 71%
“…The Daihaidao Formation consists of fluvial facies sandstone and conglomerates, which can be divided into two units, an upper unit and a lower unit (Figure ). Pterosaur fossils were discovered in the lower unit, indicating that it is of late Early Cretaceous age (Wang, Kellner, et al, ). Detailed sedimentary facies are shown in Figure .…”
Section: Geological Settingmentioning
confidence: 99%
“…Therefore, the most probable source for these sediments is the Early Triassic granites in the Harlik mountain. Thermochronological studies show that these granites started being exhumed by the Early Cretaceous with AFT ages mostly ranging from ~ 141 to 90 Ma (Gillespie et al, ; Zhu et al, ), simultaneous with the deposition age of the Dahaidao Formation, which was determined by the occurrence of pterosaur fossils (Wang, Kellner, et al, ).…”
Section: Interpretation Of Provenance Changesmentioning
confidence: 99%
“…Aerodynamic models of bone strength analyses and wing-loading forces have revealed that pterosaurs potentially flew with high manoeuvrability (Palmer, 2011;Habib & Hall, 2012;Habib & Witton, 2013), and likely utilised energy-efficient quadrupedal take-offs (Habib, 2008). Pterosaur phylogeny (Kellner, 2003;Unwin, 2003;Lü et al, 2010;Andres, Clark & Xu 2014), ground-based behaviours elucidated from trace fossils (ichnofossils) (Hwang et al, 2002;Xing et al, 2012;Fiorillo et al, 2015) and reproductive biology (Chiappe et al, 2004;Grellet-Tinner et al, 2007;Lü et al, 2011a;Wang et al, 2015Wang et al, , 2017 have also seen major advances. One area of pterosaur research lagging behind, however, is understanding of their dietary ecology (Unwin & Henderson, 2002;Hone, 2012;Hone et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%